Polymyxin Combination Therapy and the Use of Serum Bactericidal Titers in the Management of KPC-Producing Klebsiella pneumoniae Infections: A Report of 3 Cases - Eric Gomez; Martha Sanchez; Zonaira Gul; Carl Urban; Noriel Mariano; Robert H. K. Eng; David B. Huang; Tom Chiang (Case Reports in Medicine)
Management of patients with KPC-harboring Enterobacteriaceae has become a significant and challenging scenario. We report three cases of KPC-producing Klebsiella pneumoniae bacteremia that were successfully treated using combination therapy with polymyxin B and other antimicrobials. Serum bactericidal titers were determined and provided additional clinical guidance in the management of such patients.